Optimization of Alkaline Pretreatment and Fermentation Conditions for Improved Physicochemical Properties and Yield of Bioethanol Produced from Sugarcane Bagasse - Bosede A. ORHEVBA; Sodeeq A. OLAJIDE (FUDMA Journal of Engineering and Technology, 2025)
Selected processing parameters were optimized to determine their impact on the yield and some physicochemical properties of bioethanol derived from sugar cane (Saccharum officinarum) bagasse. Bioethanol was produced from sugar cane bagasse using alkaline pretreatment method, simultaneous saccharification and fermentation processes. The physicochemical properties determined were: Density, kinematic viscosity, specific gravity, boiling point, pour point, pH value and ethanol concentration. The analytical methods used followed standard procedures. Two-way factor was used for the analysis of variance (ANOVA) to evaluate the effect of these processing parameters on the yield and physicochemical properties. The results revealed that the processing methods (alkaline pretreatment method, simultaneous saccharification and fermentation processes), had significant effect (p<0.05) on the yield and physicochemical properties of the bioethanol produced from sugar cane bagasse. The results ranged from 6.5 – 42.2% for the yield; 0.8462 – 0.9541 g/ml for density; 1.98 – 2.43 mm2/s for kinematic viscosity; 0.8462 – 0.9541 for specific gravity; 88 – 98 oC for boiling point; -8 – 2 oC for pour point; 5.2 – 8.3 for the pH value and 37.2 – 85.06% for the bioethanol concentration. In conclusion, the results suggested that 5% sodium hydroxide concentration and 7days simultaneous saccharification and fermentation process has highest yield and ethanol concentration, and it was deduced that both the sodium hydroxide concentration and fermentation independently and jointly have significant effect on the yield and physicochemical properties. The favourable results obtained for the physicochemical properties of the bioethanol also suggested that it can find use as blend for gasoline.